Study on explosion risk assessment of low‐concentration gas safe combustion system based on FAHP‐fuzzy fault tree. (23rd September 2021) - Zheng, Xiaoliang; Chen, Hualiang; Xue, Sheng; Zheng, Chunshan; Qi, Feilong
Abstract: Explosion is the most dangerous accident during direct combustion of low‐concentration gas. Few investigations have focused on explosion risk assessment of low‐concentration gas safe combustion system. This study aims to analyze explosion risk of above system. Due to insufficient accident data for calculating the failure probability of explosion, expert evaluation method and fuzzy algorithm were adopted to obtain the failure probability of basic events (BEs) and Fuzzy Analytic Hierarchy (FAHP) Process method used to improve the calculation of expert weights. Then qualitative and quantitative analysis was carried out using fault tree analysis. Results show that the failure probability of system explosion is 0.085%. Events with high‐risk probability are mainly on equipment management and personnel behavior norms. Safe combustion system has excellent performance on tempering prevention, explosion resistance and explosion relief. The outcomes of this study are expected to help the safety professionals while formulating safety management measures for low‐concentration gas safety combustion system.